Designing multifunctional ferromagnetic high-entropy shape memory alloys (FHESMAs): Cr and Mn influence on structural, physical, magnetic and nuclear radiation shielding in NiFeGaCo alloys - Ozkul, Iskender; Karaduman, Oktay; Simsek, Tuncay; Simsek, Telem; Canbay, Canan Aksu; Guler, Omer; Tekin, H. O. (Elsevier, 2025)
This study systematically investigates the influence of Cr and Mn additions on the structural, magnetic, and radiation shielding properties of NiFeGaCo-based ferromagnetic high-entropy shape memory alloys (FHESMAs) synthesized via the arc melting method. The fabricated NiFeGaCo, NiFeGaCoCr, and NiFeGaCoMn alloys were comprehensively characterized in terms of their phase formation, microstructure, martensitic transformation behavior, and magnetic performance. The results demonstrated that Mn addition significantly improved the magnetic properties, yielding the highest saturation magnetization (56.64 emu/g) and lowest coercivity (5.55 Oe), making NiFeGaCoMn highly suitable for soft magnetic applications. In contrast, Cr addition provided moderate magnetic behavior but enhanced structural stability with the largest crystallite size and lowest lattice strain. Moreover, gamma-ray and fast neutron shielding investigations revealed that the Cr-containing alloy exhibited superior performance in terms of linear attenuation coefficient, half-value layer, effective electron density, and fast neutron removal cross-section values, while Mn addition slightly reduced these shielding capabilities. It can be concluded that Cr addition offers a balanced advantage in designing FHESMAs with combined magnetic sensitivity and radiation shielding efficiency, whereas Mn addition is more effective for maximizing magnetic performance with a compromise in shielding characteristics.
Keywords: High-entropy alloys (HEAs); Ferromagnetic shape memory alloys (FHESMAs); NiFeGaCo; Martensitic transformation; Magnetic properties; Neutron and Gamma-ray attenuation